EU public construction law - Vomáčka, Vojtěch, 1984-; Munipress (nakladatelství); Masarykova univerzita. Katedra práva životního prostředí a pozemkového práva (Brno : Masaryk University Press, 2025)
The monograph traces the degree of indirect harmonisation of spatial planning and planning permission in EU law and the scope of the relevant requirements. It focuses on the gradual development of EU law, the relationships, differences and synergies between the different conditions in order to provide a more comprehensive picture, and then concentrates on the most critical issues identified, namely the interpretation of the general concepts used in environmental legislation and the explanation of the content of the public participation requirements. It also examines the relationship between the Aarhus Convention and EU law, highlighting the fundamental guarantees of participation in decision-making and access to justice. Furthermore, the monograph analyses the requirements for planning and construction arising from so-called non-environmental EU policies. It focuses in particular on the development of cohesion policy and the urban agenda, maritime spatial planning, the development of the TEN-T and TEN-E networks, requirements for building materials, energy efficiency in buildings and the promotion of renewable energy.";EU public construction law"
Publikace analyzuje právní rámec Evropské unie v oblasti územního plánování a stavebního práva s důrazem na míru jejich nepřímé harmonizace. Autor se zaměřuje na vývoj relevantních právních norem, jejich vzájemné vztahy a interpretaci klíčových pojmů, zejména v kontextu práva životního prostředí. Pozornost je věnována také požadavkům na účast veřejnosti a přístupu k právní ochraně, včetně vztahu k Aarhuské úmluvě. Kniha dále zkoumá vliv dalších politik EU, jako je kohezní politika, energetika či rozvoj transevropských sítí, na regulaci výstavby a územního rozvoje.
"MUNI PRESS"—Zadní strana obálky
Pod názvem: Department of Environmental Law and Land Law, Faculty of Law, Masaryk University
Obsahuje bibliografické odkazy
Keywords: stavební právo; evropské právo; harmonizace práva; územní plánování; politiky Evropské unie; země Evropské unie; monografie; building law; European law; harmonization of laws; spatial planning; European policies; European Union countries; monographs